Penentuan Harga Jual Bedetan Ikan Pada Kelompok Wanita Tani (KWT) Bedetan Perancak Di Desa Perancak - Gayatri, Ida Ayu Devi Ananda; Dewi , Ni Wayan Yulianita (Universitas Pendidikan Ganesha, 2022)
This study aims to identify the selling price of bedetan (dry fish) food product on women farming group in Perancak village and to find out whether the determined price could give profit for the group. The study was designed in the form of descriptive qualitative study. The data of this study were obtained by conducting observation, interview and documentation with two informants who were the group leader and one of the members who was incharge in bedetan production from women farming group in Perancak village. Furthermore, the obtained data were analyzed by using data analysis techniques including data reduction, data presentation and drawing conclusion. The result of this study shows that (1) In determining the selling price, it was not in accordance with the criteria of the cost of production and the determination of selling price theories due to lack of knowledge about accounting. Therefore, there were several costs that were not taken into account when determining the cost of production. (2) The result based on cost plus pricing method was low because of the difference in the costing from the beginning in the cost of production calculation. (3) The result of selling price used by both of the women farming group in Perancak village and the Cost Plus Pricing method gave profit for the group. Meanwhile, it was more accurate to use the Cost Plus Pricing method so that the group could charge all costs that affected the production processes of bedetan (dry fish) food product.